Strength of WC-Co hard metals as a function of the effectively loaded volume. (April 2017) - Jonke, M.; Klünsner, T.; Supancic, P.; Harrer, W.; Glätzle, J.; Barbist, R.; Ebner, R.
Abstract: WC-Co hard metals show defect-controlled fracture behaviour. This means that the fracture stress under tensile loading conditions is directly related to the size of the largest defect within the loaded volume. The size distribution of these defects relevant to failure under static and cyclic loading conditions can be quantitatively described by Weibull statistics. Prior studies on the fracture behaviour of hard metals and the nature and size of material inhomogeneities, i.e. defects, do not attain their data from one single batch of material. To avoid uncertainties from possible variations in material composition the current work studies the fracture behaviour of a single material batch as a function of the effectively loaded volume V eff . A variety of specimen geometries and loading arrangements was applied in order to vary V eff over five orders of magnitude. Fracture stress values are found to increase from about 1500 MPa to 4200 MPa while decreasing the effectively loaded volume from about 100 mm 3 down to about 0.01 mm 3 . The observed volume effect of strength shows the expected qualitative trends with quantitative deviations from Weibull-like strength behaviour. The presence of two different kinds of defects in the form of pores and single enlarged WC grains on the attained fracture surfaces, as found by a fractographic analysis in the SEM, is a possible explanation for this observation. Information provided by the current study is the basis for the judgment of the relevance of volume defects regarding the failure of tools or structural components made of WC-Co hard metals under certain loading conditions. Highlights: Statistically sound information on the defect size distribution in hard metals. All data for a certain hard metal grade variant from one single material batch. Variation on the effectively loaded volume V eff over five orders of magnitude. Deviations from Weibull-like strength distribution observed. Fractography reveals two different kinds of defects at different V eff values.